The Effect Of Service Quality On Redpack Labeled Cargo Delivery Services On Customer Satisfaction Of PT. PELNI (Persero) Head Office In 2024 - Rahmayanti, Henita; Sahara, Siti; Putri Galuh, Deary Tree Nowi (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
This research aims to find out how much influence and what factors most influence customer satisfaction in the quality of service for cargo labeled Redpack at PT PELNI (Persero) Head Office. With a quantitative method, sampling was carried out on RedPack cargo customers using a saturated sampling technique, taking the entire population as a sample, namely 70 respondents. The data obtained through the questionnaire was analyzed using simple linear regression and correlation to find out how much influence the variables have, while to find out the factors that most influence customer satisfaction in service quality using the results of respondents' answers to service quality distributed through the questionnaire. The results of simple linear regression analysis show that there is a positive and significant influence between service quality and customer satisfaction, and the correlation results show that the influence of service quality on customer satisfaction is 53.7The results of the questionnaire show that the factor that most influences customer satisfaction is the quality of service at the Redpack labeled goods delivery service at PT. Pelni (Persero) in 2024 is reliability or greatness of service. From the results of the partial T test hypothesis testing, it is known that the significant level is 0.001 < 0.05, it is stated that Ho is rejected and Ha is accepted, which means that service quality has a significant effect on customer satisfaction with RedPack cargo at PT. Pelni (Persero)